Фізичні основи процесів самовідновлення конденсаторів - Черних, В. Д. (ХНУРЕ, 2024)
The principle of operation of self-healing capacitors is shown. Examples of situations in which this ability can be realized are given. The advantages and disadvantages of self-healing capacitors are named. The characteristics and features of the capacitors self-healing process are considered.
Keywords: конденсатор